Relationship Determinants of Cadre Roles in Parenting Services for Toddler Families in Jambi City - Andi Subandi; Dwi Noerjoedianto (International Journal Of Health Science, 2022)
Toddlerhood is a golden era in children's growth and development because it is a period of real growth that influences and determines children's subsequent development. Through the Toddler Family Development (Bina Keluarga Balita/BKB) movement. Every family would be able to enhance their talents, particularly in caring for their toddlers and pre-school-aged children, to promote optimum child growth and development. Health cadres play a significant role in efforts to strengthen the community's capacity to reach optimal health status independently. This study seeks to identify the elements that influence the involvement of cadres in providing family care services for toddlers in the city of Jambi. This study used a quantitative, cross-sectional methodology. This study's population consisted of 450 cadres from the Toddler Family Development (Bina Keluarga Balita/BKB) program. This study's sample consisted of 81 the Toddler Family Development (Bina Keluarga Balita/BKB) cadres selected using Probability Sampling with Proportional Stratified Random Sampling. The chi-square test demonstrates that there is a correlation between the variables attitude (p-value = 0.001) and motivation (p-value = 0.002). Moreover, there is no correlation between knowledge and BKB cadres' roles (p-value = 0.180). Attitude and motivation variables are substantially associated with the role of the Toddler Family Development (Bina Keluarga Balita/BKB) Cadres in Jambi City. The Office of Population Control and Family Planning will hold online discussions. Hence, cadres are always aware of the most recent developments in activities of the Toddler Family Development (Bina Keluarga Balita/BKB). The Office of Population Control and Family Planning will monitor activities even when not on the ground. The Office of Population Control and Family Planning will reproduce books on the Toddler Family Development (Bina Keluarga Balita/BKB) so cadres can gain more knowledge and not rely solely on training experience.